Performance Analysis of Non-Isolated DC-DC Buck Converter Using Resonant Approach - Jayaswal, K.; Palwalia, D. K. (Engineering, Technology & Applied Science Research, 2018)
DC-DC converters preserve or control the output DC voltage. Due to parasitic constituents such as leakage capacitance of both diode and inductor, and transformer leakage inductance, DC-DC converters mostly operate on rigid switching conditions which result in high switching losses. These parasitic constituents affect the dc-dc converter’s operational reliability, instigate electromagnetic interference issues and limit the converter’s operation at higher frequency operations. In this paper, resonant or soft-switch approach has been employed to improve the operating performance and design-oriented principle investigations have been carried out for overcoming the issues of parasitic constituents in 24-12V DC-DC step-down (buck) converter. This paper divulges the analysis and Matlab Simulation results for 24-12V buck converter based on resonant or soft-switching approach.